Low voltage and high ON/OFF ratio field-effect transistors based on CVD MoS2 and ultra high-k gate dielectric PZT1. Issue 19 (21st May 2015) - Zhou, Changjian; Wang, Xinsheng; Raju, Salahuddin; Lin, Ziyuan; Villaroman, Daniel; Huang, Baoling; Chan, Helen Lai-Wa; Chan, Mansun; Chai, Yang
<x xml:space="preserve">Abstract</x> Ultra high-k dielectric enables low-voltage enhancement-mode MoS2 transistor with high ON/OFF ratio, leading to low-power device.